Organizational communication management in effective Islamic school - Rengkaningtias, Ayu Usada; Hanum, Farida; Abd Jabar, Cepi Safruddin (Universitas Negeri Yogyakarta, 2025)
Management and communication are two vital things an educational institution needs to pay attention to to achieve organisational goals. Communication helps managerial functions to run effectively. Important communication is in every stage of the management function, from planning, organizing, actuating, and controlling. In addition, communication guarantees that there is no interruption of information in every management, including educational institutions such as schools. This paper seeks to explore and obtain information about organizational communication management. The type of research used in this paper is literature research (literary study) in which theory is taken from library data and then studied and examined in obtaining contents to obtain objective results. A literature study found that a school has several organisational communication management strategies that are optimal and effective in achieving organisational goals, including those of Islamic schools. First, in order to be an effective school, all systems in an organisation must carry out their respective functions properly. Second, whatever the pattern of organisational communication in schools, the most important thing in an organisation is the direction of communication that is able to accommodate the flow of information. Third, to become an effective school, school management must be able to overcome communication barriers with various strategies. Fourth, religious values play an important role in the context of Islamic schools through prophetic communication. This will form a noble culture of Islamic educational organizations that support organizational communication management so that a school transforms into an excellent and effective school. Manajemen dan komunikasi adalah dua hal vital yang perlu diperhatikan sebuah lembaga pendidikan dalam mencapai tujuan organisasi. Komunikasi membantu fungsi-fungsi manajerial agar berjalan dengan efektif. Komunikasi penting berada dalam setiap tahapan fungsi manajemen, mulai dari planning (perencanaan), organizing (pengorganisasian), actuating (implementasi/ pelaksanaan), dan controlling (pengawasan). Selain itu, komunikasi menjamin tidak adanya keterputusan informasi dalam setiap manajemen, termasuk lembaga pendidikan seperti sekolah. Tulisan ini berupaya menggali dan mendapatkan informasi mengenai manajemen komunikasi organisasi di sekolah, termasuk di sekolah Islam. Jenis penelitian yang digunakan dalam tulisan ini adalah literature research (studi literatur) dimana teori diambil dari data-data kepustakaan lalu dikaji dan ditelaah dalam memperoleh konsepsi untuk mendapatkan hasil yang objektif. Penelitian ini menemukan bahwa ada sejumlah strategi manajemen komunikasi organisasi di sebuah sekolah agar optimal dan efektif dalam mencapai tujuan organisasi. Pertama, agar menjadi sekolah yang efektif seluruh sistem dalam sebuah organisasi harus menjalankan masing-masing fungsinya dengan baik. Kedua, apapun pola komunikasi organisasi yang diterapkan di sekolah, hal terpenting dari sebuah organisasi adalah bagaimana arah komunikasi dalam pola tersebut mampu mewadahi seluruh kelancaran informasi. Ketiga, untuk menjadi sebuah sekolah yang efektif, manajerial sekolah harus mampu mengatasi hambatan komunikasi dengan berbagai macam strategi. Keempat, ada peran penting dari nilai-nilai agama dalam konteks sekolah Islam dalam bentuk komunikasi profetik akan membentuk budaya mulia organisasi pendidikan Islam yang mendukung manajemen komunikasi organisasi sehingga sebuah sekolah bertransformasi menjadi sekolah yang unggul dan efektif.